2012
DOI: 10.5152/balkanmedj.2012.051
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity in Elementary Schools in Mardin, South-Eastern of Turkey: A Preliminary Study

Abstract: Objective: This research determines the frequency of obesity among primary school-aged children and evaluates the relationship between obesity and family and environmental factors.Material and Methods: Three thousand four hundred sixty students, aged 6-15 years in three primary schools in Mardin city center were taken into the study. Information about eating habits and family-environmental factors were obtained by questionnaire. For each student we calculated the body mass index (BMI) and the ≥97 percentile wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…We found that obesity was more prevalent in the high SES group compared to low and medium-SES groups. This finding was consistent with another recent report from Mardin in southeastern Turkey (10). Similarly, in a review of childhood obesity across Middle Eastern countries, Mirmiran et al (22) concluded that the relationship between SES and obesity was complex and varied across different cultures; they found obesity to be more prevalent in urban areas and higher SES in some countries such as Egypt, while it is more prevalent in medium SES in countries such as Pakistan, suggesting perhaps different stages of the nutrition transition across countries.…”
Section: N=2066supporting
confidence: 94%
See 1 more Smart Citation
“…We found that obesity was more prevalent in the high SES group compared to low and medium-SES groups. This finding was consistent with another recent report from Mardin in southeastern Turkey (10). Similarly, in a review of childhood obesity across Middle Eastern countries, Mirmiran et al (22) concluded that the relationship between SES and obesity was complex and varied across different cultures; they found obesity to be more prevalent in urban areas and higher SES in some countries such as Egypt, while it is more prevalent in medium SES in countries such as Pakistan, suggesting perhaps different stages of the nutrition transition across countries.…”
Section: N=2066supporting
confidence: 94%
“…Recent studies suggest between 20-25% of youths aged 6-19 years are overweight or obese in Turkey (7)(8)(9), but numbers in the largest metropolitan areas of Turkey are not clear. There could be significant variations in the prevalence of child obesity in Turkey, as regional eating habits and the physical activity environment differ across the country (10).…”
Section: Introductionmentioning
confidence: 99%
“…Over the previous two decades childhood obesity in Turkey increased from 6-7% to 15-16% [33]. In Turkey there are studies performed at the local level covering various geographical regions of the country [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. A summary and a comparison of the results of available studies on adolescent obesity are shown on Table 2.…”
Section: Obesity Among Children and Adolescents A State Inducing Cvdmentioning
confidence: 99%
“…If childhood obesity reaches to adulthood then it leads to serious increases in morbidity and mortality due to complications such as metabolic syndrome, type 2 diabetes, hypertension, hyperlipidemia, cardiovascular disease and certain types of cancers (colon, breast, gall bladder, and endometrium). The fact that most of these complications are preventable indicates that obesity is a health problem that should be considered even from childhood (9,10) .…”
Section: Introductionmentioning
confidence: 99%